Motivación escolar en la realización de tareas de lenguaje y literatura de los estudiantes de décimo año de educación básica del colegio nacional técnico Dr. Demetrio Aguilera Malta de la ciudad de Santa Rosa provincia de El Oro, año lectivo 2012-2013. - Sánchez Andrade, Giovanna Isabel (2013)
This thesis entitled SCHOOL GROUNDS IN THE CONDUCT OF TASKS FOR LANGUAGE AND LITERATURE sophomore year of basic education NATIONAL TECHNICAL COLLEGE DR. Demetrio Aguilera Malta OF THE CITY OF SANTA ROSA province of El Oro 2012 is about the importance of motivation in school performance and their influence on learning. Previously he built the theoretical framework to support theoretically the subject under study. Below is a brief description of the institution where the research took place to get familiar with the field educational context because of our interest.